폐를 침범한 피부근염/다발성근염의 임상적 양상 - 박근민; Park Geun Min; 최창민; Choe Chang Min; 엄상원; Eom Sang Won; 황용일; Hwang Yong Il; 임재준; Im Jae Jun; 이재호; Lee Jae Ho; et al. (Tuberculosis and respiratory diseases, 2001)
Background : Although lung involvement has been reported in 5 to 46% of dermatomyositis/polymyositis(DM/PM) patients, reports of the condition in Korea are rare. This study evaluated the clinical features of lung involvement in DM/PM patients. Methods : The medical records, laboratory results and radiologic findings of 79 DM/pM patients, who attended the Seoul National University Hospital (SNUH) between 1989 and 1999, were reviewed retrospectively. Results : A total 79 patients of whom 24 patients(33%) showed lung involvement, were enrolled in this study. More patients with lung involvement were female(F:M=11:1), and older compared with those without lung involvement. Patients with lung involvement presented with dyspnea(79%), coughing(67%), an elevated ESR, and CK/LD. Anti-Jo 1 antibody test was positive in 30%, which is significantly higher in patients with lung involvement. A simple chest X-ray of the patients with lung involvement exhibited reticular opacity(50%), reticulonodular opacity(30%), patchy opacity(29%), nodular opacity(13%) and linear opacity(4%). HRCT(n=24) showed ground glass opacity(75%), linear or septal thickening(50%), patchy consolidation(42%), honey-combing(33%) and nodular opacity(17%). The pulmonary function test showed a restrictive ventilatory pattern(77%) and a lower diffusing capacity(62%). The patients were followed up during a mean duration of $30{±}28$ months. They were treated with steroid only(50%) or a combination of steroids and cytotoxic agents(46%). Muscle symptoms were improved in 89% with treatment, but an improvement in the respiratory symptoms or in the pulmonary function test was rare. Patients with lung involvement had a higher mortality rate(21%) than those without lung involvement(10%) during the follow-up periods. Conclusion : DM/PM patients with lung involvement were mostly female, older and had a higher positive rate Anti-Jo 1 antibodies, but there was no significant difference in prognosis. 연구배경 : 피부근염/다발성근염 환자의 폐침범에 대한 국내의 보고는 드물며, 이에 폐를 침범한 피부근염/다발성근염 환자의 임상상을 살펴보았다. 방 법 : 1989년부터 1999년까지 서울대병원을 내원한 피부근염/다발생근염 환자의 임상양상과 방사선검사를 포함한 검사소견을 후향적으로 분석하였다. 결 과 : 총 79명(피부근염/다발성근염 : 54/25명)의 환자 중 24명(33%)의 환자에서 폐침범이 있었다. 폐침범이 있는 환자군의 여성비(11:1)와 연령($50{±}13$세)이 높았다. 폐침범이 있는 환자에서 호흡곤란(79%)과 기침(67%)의 증상이 있었고, ESR이 $47{±}7\;mm/hr$, CK/LD가 $2169{±}820/577{±}61\;IU/L$로 증가하였다. Anti-Jo1 Ab는 30%에서 양성이었다(p-value : 0.03). 흉부 HRCT 상 망상 또는 간유리 음영(9%), 선상 음영 또는 중격 비후(50%), 반점상 경화(38%), 벌집낭(33%), 결절 음영(17%)으로 관찰되었다. 환자는 $30{±}28$개월 동안 추적관찰 되었고, 스테로이드 단독치료(46%)와 면역억제제 병행치료(50%)를 받았다. 경과 중 사망률은 폐침범이 있는 군(21%)에서 폐침범이 없는 군(10%)보다 높은 경향을 보였다.